2009
DOI: 10.4049/jimmunol.0901017
|View full text |Cite
|
Sign up to set email alerts
|

Protumor vs Antitumor Functions of IL-17

Abstract: Inflammation appears to be a necessity for both metastasis and elimination of tumor cells. IL-17, a proinflammatory cytokine produced by Th17 cells, contributes to both the processes by playing a dual role in the antitumor immunity. On one hand, IL-17 promotes an antitumor cytotoxic T cell response leading to tumor regression. On the other hand, by facilitating angiogenesis and egress of tumor cells from the primary focus, IL-17 promotes tumor growth. Thus, the therapeutic application that uses IL-17 needs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(293 citation statements)
references
References 111 publications
11
280
1
1
Order By: Relevance
“…Despite the positive correlation of Th17 cells with reduced survival in HCC cases, the role of these cells in HCC still remains incompletely defined. Some studies have recently suggested that IL17 plays a dual role in tumor immunology; it can either promote antitumor cytotoxic T cell responses or foster angiogenesis of surrounding endothelial cells and fibroblasts facilitating tumor growth [52] . In HCC patients, increased levels of Th17 and Th1 cells were observed in tumor regions as compared to nontumor regions, with the frequency of these cells being associated with overall diseasefree survival [53] .…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Despite the positive correlation of Th17 cells with reduced survival in HCC cases, the role of these cells in HCC still remains incompletely defined. Some studies have recently suggested that IL17 plays a dual role in tumor immunology; it can either promote antitumor cytotoxic T cell responses or foster angiogenesis of surrounding endothelial cells and fibroblasts facilitating tumor growth [52] . In HCC patients, increased levels of Th17 and Th1 cells were observed in tumor regions as compared to nontumor regions, with the frequency of these cells being associated with overall diseasefree survival [53] .…”
Section: T Lymphocytesmentioning
confidence: 99%
“…These cells and the cytokines they produce (including IL-17A, IL-17F and IL-22) have been shown to play important roles in the pathogenesis of autoimmune diseases and inflammation [49,50]. Their biological role in the tumor microenvironment is poorly understood, and at present suggested to be both beneficial and detrimental to the cancer patient [51]. The generation and regulation of T H 17 cells in ovarian cancer have been documented [45] and the possible function and clinical relevance of these cells in human tumor microenvironments reported [46].…”
Section: Inflammatory Leukocytes In the Tumor Microenvironmentmentioning
confidence: 99%
“…(4). The prevalence of Th17 cells was found to increase in the tumor microenvironment during tumor development (5). In addition, IL-17 plays a prominent role by increasing the angiogenic activity (6) via certain indirect mechanisms, such as (i) induction of IL-17-responsive cells to secrete proinflammatory cytokines, e.g., IL-6 and IL-1β, which also possess potent angiogenic activity (7); (ii) induction of a wide range of angiogenic mediators but inhibition of the angiostatic chemokine secretion (8); and (iii) induction of tumor and epithelial cells to secrete increasing levels of angiogenic chemokines (9).…”
mentioning
confidence: 99%